Genomic characterization of carbapenem-resistant Klebsiella oxytoca complex in China: a multi-center study - Wan, Weimin; Yang, Xiaochun; Yu, Hua; Wang, Min; Jia, Wei; Huang, Bin; Qu, Fen; Shan, Bin; Tang, Yi-Wei; Chen, Liang; Du, Hong (Frontiers in Microbiology, 2023)
Carbapenem-resistant (CR) Klebsiella oxytoca complex can be associated with high mortality, emerging as a new threat to the public health. K. oxytoca complex is phylogenetically close to K. pneumoniae, one of most common species associated with multidrug resistance in Enterobacterales. The latest research showed that K. oxytoca is a complex of six species. Currently, the epidemiological and genomic characteristics of CR K. oxytoca complex in China are still unclear. Here, we conducted a multi-center study on 25 CR K. oxytoca complex collected from five representative regions in China. These isolates were respectively recovered from respiratory tract (12 cases, 48.0%), abdominal cavity (5 cases, 20.0%), blood (4 cases, 16.0%), urine tract (3 cases, 12.0%) and skin or soft tissue (1 cases, 4.0%). Among them, 32.0% (8/25) of patients infected with K. oxytoca complex had a poor prognosis. In this study, three K. oxytoca complex species were detected, namely K. michiganensis, K. oxytoca and K. pasteurii, among which K. michiganensis was the most common. Three carbapenemase genes were identified, including blaNDM-1 (10, 38.5%), blaKPC-2 (9, 34.6%) and blaIMP (6 blaIMP-4 and 1 blaIMP-8) (7, 26.9%). Subsequent multilocus sequence typing identified various sequence types (STs), among which ST43, ST92 and ST145 were relatively common. Different from the clonal dissemination of high-risk carbapenem-resistant K. pneumoniae strains, our research revealed a polyclonal dissemination characteristic of CR K. oxytoca complex in China. S1-nuclease PFGE and Southern blot experiment showed that carbapenemase genes were encoded in plasmids of different sizes. Two blaNDM-harboring plasmids were subsequently sequenced and were characterized to be IncX3 and IncC incompatibility groups, respectively. This is the first multi-center study of CR K. oxytoca complex in China, which improved our understanding of the prevalence and antimicrobial resistance characteristics of CR K. oxytoca complex in China.